2017
DOI: 10.1053/j.jrn.2017.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Retinol Concentration Is Mainly Driven by Transthyretin in Hemodialysis Patients

Abstract: Plasma retinol concentration is mainly driven by transthyretin in hemodialysis patients. Abstract BackgroundMicronutrients deficiencies in hemodialysis patients are due to low dietary intakes and intradialytic losses for hydrophilic micronutrients. Conversely, lipophilic non-dialyzable compounds might accumulate due to a lack of elimination through renal metabolism or dialysis. Other compounds have complex metabolism: their concentration is not explained by these phenomenons. Study design Monocentric observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Increased serum retinol levels in CKD patients are also sufficient for inducing the expression of GPR68 and inflammatory cytokines in human monocytes. As lipophilic non-dialyzable compounds, including retinol, often accumulate in CKD patients due to a lack of elimination through renal metabolism and dialysis 83 , development of a strategy to suppress retinol accumulation will be useful to prevent the cardiac complications of CKD.…”
Section: Discussionmentioning
confidence: 99%
“…Increased serum retinol levels in CKD patients are also sufficient for inducing the expression of GPR68 and inflammatory cytokines in human monocytes. As lipophilic non-dialyzable compounds, including retinol, often accumulate in CKD patients due to a lack of elimination through renal metabolism and dialysis 83 , development of a strategy to suppress retinol accumulation will be useful to prevent the cardiac complications of CKD.…”
Section: Discussionmentioning
confidence: 99%
“…The association between plasma retinol and mortality risk has been previously examined in several studies; however, the findings are inconsistent. Espe et al, 17 Bataille et al, 18 and Kalousová et al 8 suggested that decreased retinol is associated with increased mortality risk in hemodialysis patients. Connolly et al 7 found that a lower retinol level was an independent predictor of all‐cause mortality.…”
Section: Discussionmentioning
confidence: 99%